Tinjauan Layanan Anak di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Silalahi, Katarina Debora; Primadesi, Yona (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the review services children in the Library and Archives of West Sumatra province. By analyzing the data, we can conclude the following. First, the implementation of children's services at the Library and Archives of West Sumatra Province conducted in 2012 which is a coloring and writing articles, but other events such as film screenings and storytelling can not be implemented due to various conditions that do not allow; The next complete collection of the amount due each year receive additional collections; This service facilities are not complete; and interest in reading children who are less affected by the proliferation of internet access. Second, while the presence of obstacles in the implementation of children's services such as limited facilities, the transfer of funds, as well as indoor conditions that lead to not all activities can be carried out. Third, efforts that can be implemented to overcome the obstacles that still perform services with children, doing the distribution of funds to the two services, and plan for children's services programs in each year with reference to the evaluation in the previous year. Keywords: review; service; libraries and archives